Novel Osmoprotective DOPC-DMPC Liposomes Loaded with Antihypertensive Drugs as Potential Strategy for Glaucoma Treatment - Miriam Ana González-; José Javier López-Cano; Irene Bravo-Osuna; Vanessa Andrés-Guerrero; Marta Vicario-; Manuel Guzmán-Navarro; José Manuel Benítez-; Rocío Herrero-Vanrell; Irene Teresa Molina-Martínez (MDPI AG, 2022)
Glaucoma is a group of chronic irreversible neuropathies that affect the retina and the optic nerve. It is considered one of the leading causes of blindness in the world. Although it can be due to various causes, the most important modifiable risk factor is the elevated intraocular pressure (IOP). In this case, the treatment of choice consists of instilling antihypertensive formulations on the ocular surface. The chronicity of the pathology, together with the low bioavailability of the drugs that are applied on the ocular surface, make it necessary to instill the formulations very frequently, which is associated, in many cases, with the appearance of dry eye disease (DED). The objective of this work is the design of topical ocular formulations capable of treating glaucoma and, at the same time, preventing DED. For this, two liposome formulations, loaded with brimonidine or with travoprost, were Tadeveloped using synthetic phospholipids and enriched by the addition of compounds with osmoprotective activity. The proposed formulations not only presented physicochemical characteristics (size, pH, osmolarity, surface tension, and viscosity) and encapsulation efficiency values (EE% of 24.78% and ≥99.01% for brimonidine and travoprost, respectively) suitable for ocular surface administration, but also showed good tolerance in human corneal and conjunctival cell cultures, as well as an in vitro osmoprotective activity. The hypotensive effect of both liposomal formulations was evaluated in normotensive albino New Zealand rabbits, showing a faster and longer lasting reduction of intraocular pressure in comparison to the corresponding commercialized products used as control. According to these results, the hypotensive liposomal formulations combined with osmoprotective agents would result in a very promising platform for the treatment of glaucoma and the simultaneous protection of the ocular surface.